(untitled) (Comparative & International Education Series, 2022)
I came into graduate school in the United States of America as a Fulbright scholar. There was a sense of pride coming into the academic program. Having worked for 5 years as an educator, I felt I had this new experience under control. In fact, the odds were stacked in my favor to excel. I did three years’ worth of undergraduate studies in the UK - the University of Portsmouth - to be exact. So, living in a foreign country? Checked. Also, I did not go back home for the entire duration of the three years. Homesick? Checked. I fared fairly well in terms of academics– got an A for my thesis. Academic excellence? Checked. I also worked in the UK for a bit, so international experience. Checked!